Research Progress on the Effect of Heat Treatment on Soy Protein Structure and Emulsions - Xiuqing ZHU; Ying GAO; Xihuan XUAN; Tianlu HAN; Ying ZHU; Yuyang HUANG; Yuxin FU (Shipin gongye ke-ji)
In recent years, soybean protein is widely used in industries such as food, medicine, and cosmetics due to its unique nutritional value and excellent emulsifying properties. However, the application of soybean protein as an emulsifier is somewhat limited. Therefore, modification treatments have become essential measures to enhance its emulsifying capacity. Heat treatment, as a common processing method, can cause the denaturation and aggregation of soybean protein, significantly affecting its structure and functionality, thereby potentially improving the emulsifying properties and stability of soybean protein emulsions. This article reviews the preparation of soybean protein emulsions and the effects of heat treatment on the secondary structure, subunits, particle size and zeta potential, and properties of soybean protein emulsions. It focuses on analyzing their roles in emulsification, emulsion stability, rheological properties, and interfacial characteristics. Additionally, the potential applications of soy protein emulsions in 3D printing, active substance delivery, and bioplastics are explored. Finally, suggestions for optimizing heat treatment techniques and their applications are proposed to support the further development of soybean protein emulsions.